2023
DOI: 10.3389/fimmu.2023.1153851
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of neutrophil extracellular traps in endometritis

Abstract: Endometritis is a kind of common obstetric disease in women, usually caused by various pathogenic bacteria. Neutrophil infiltration is one of the most important pathological features of endometritis. Neutrophils can reach the uterine cavity through the endometrium, and make early response to the infection caused by the pathogen. Neutrophil extracellular traps (NETs), a meshwork of chromatin fibers extruded by neutrophils, have a role in entrapping microbial pathogens. It has been confirmed that NETs have a str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The NETs-related lncRNAs (NETsLnc) signature efficiently predicts prognosis and immune infiltration in different tumors. Liu et al [56 ▪ ] identified the NETsLncs signature using the weighted gene co-expression network analysis (WGCNA) algorithm and employed machine learning algorithms to create a prognostic signature. In the prediction of survival for patients with STS, NETsLnc characteristics consistently performed well.…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 99%
See 1 more Smart Citation
“…The NETs-related lncRNAs (NETsLnc) signature efficiently predicts prognosis and immune infiltration in different tumors. Liu et al [56 ▪ ] identified the NETsLncs signature using the weighted gene co-expression network analysis (WGCNA) algorithm and employed machine learning algorithms to create a prognostic signature. In the prediction of survival for patients with STS, NETsLnc characteristics consistently performed well.…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 99%
“…Patients with a high NETsLnc score displayed more genetic alterations and responded better to vincristine. In conclusion, the NETsLnc signature proves to be a promising prognostic tool for STS, enhancing our understanding of the disease and supporting more targeted and successful treatment [56 ▪ ]. However neither of these tools were tested against clinical variables or nomograms scores, such as Sarculator.…”
Section: How To Improve Further Prognostication Of All Sarcomas: Inte...mentioning
confidence: 99%